Agricultural Land Destruction Due to the Home Ownership Credit Development Policy in Jayapura City from 2022 to 2023 - Snanfi, Ferinandus Leonardo (Universitas Padjadjaran, 2025)
This study examines agricultural land degradation resulting from the home ownership credit development policy in Koya Barat Subdistrict, Jayapura City, during 2022–2023. Jayapura City has 2,135.31 hectares of agricultural land, of which 1,211.5 hectares were damaged following the construction of 25,040 housing units financed through home ownership credit in 2022. Drawing on top-down policy implementation theory, agricultural land theory, and government economic investment theory, this qualitative study analyzed data from 25 informants, including farmers, housing developers, traditional leaders, government officials, and traders. Data were collected through interviews, observation, and documentation. The findings indicate that agricultural land degradation increased to 104,496 hectares as housing credit development expanded to 116,080 units in 2023, resulting in extensive conversion of agricultural land into residential areas. The study recommends halting permits for housing construction on agricultural land, as land conversion has contributed to rising agricultural commodity prices in Jayapura City markets.